2020
DOI: 10.3390/ijerph17134641
|View full text |Cite
|
Sign up to set email alerts
|

A Reflection on Controversial Literature on Screen Time and Educational Apps Use in 0–5 Years Old Children

Abstract: Over the last five years, there has been a significant increase in screen time and apps usage by children under five years old. The considerable growth in usage by very young children has not corresponded to conclusive and consistent research investigating its possible benefits and risks. This article proposes a brief overview of recent results in this field, specifically focusing on the use of educational apps and their positive, null, and/or negative outcomes on young children’s cognitive, emotional, and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…While the research on the impacts of screen time on children's development is ambiguous and often contradictory (Cerniglia and Cimino 2020;boyd 2016), it is notable that, as with convenience foods, as mothers gain time through efficiencies in the household, these options are quickly and deeply maligned. In other words, the fact that even relatively young children can keep busy using screens is quickly re-storied as evidence of maternal failing.…”
Section: Articulating Good Motherhoodmentioning
confidence: 99%
“…While the research on the impacts of screen time on children's development is ambiguous and often contradictory (Cerniglia and Cimino 2020;boyd 2016), it is notable that, as with convenience foods, as mothers gain time through efficiencies in the household, these options are quickly and deeply maligned. In other words, the fact that even relatively young children can keep busy using screens is quickly re-storied as evidence of maternal failing.…”
Section: Articulating Good Motherhoodmentioning
confidence: 99%
“…Children develop language faster when supported by responsive parents within their early years, and excessive screen time is detrimental to development and behavior because of overstimulation, disorganization, dysregulation and distress [ 8 , 26 , 33 – 40 ]. These can disrupt interaction with people, which limits a child’s practice of verbal and nonverbal social exchanges [ 27 ]. This study observed decreased scores in receptive and expressive language when children had more than 2 h of screen time.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that the relationship between SB and EF in preschoolers is controversial [14,40], partly due to the type of SB performed, and to the time spent being sedentary. The technology advances, and the easier access to electronic devices may predispose early age children to a greater amount of time exposed to screens [41], though speci c educational TV, tablet, and computer programs developed for this public may positively contribute to children's learning process [42].…”
Section: Discussionmentioning
confidence: 99%